2021
DOI: 10.1128/msystems.00319-21
|View full text |Cite
|
Sign up to set email alerts
|

Facial Skin Microbiota-Mediated Host Response to Pollution Stress Revealed by Microbiome Networks of Individual

Abstract: The association between the skin microbiome and skin health has been widely reported. However, the role of the skin microbiome in mediating skin physiology remains a challenging and yet priority subject in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Single sample networks were produced following methodologies described previously 27 . The production of n-1 networks facilitates the analysis of networks at the subject level and additionally allows improved statistical analysis of associated network metrics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single sample networks were produced following methodologies described previously 27 . The production of n-1 networks facilitates the analysis of networks at the subject level and additionally allows improved statistical analysis of associated network metrics.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that a high level of inter-individual variation occurs in the human skin microbiome in particular with regards to less dominant community members 4 . Recently, methodologies have been developed to examine microbiome networks at an individual level to facilitate the examination of an individual’s response to intervention 27 . Examination of single sample networks showed that all study subjects showed improvement in commonly used network analysis metrics including mean degree, edge number, node number and network robustness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-occurrence network analyses based on metagenomic and amplicon sequences have been frequently used to infer microbial relations in environmental or host microbiomes, and further predict microbial interactions (positive or negative) in these environments 9 , 23 , 24 , 40 , 41 , which are informatic for discovering the true microbial interactions attributing to either microbial properties (such as metabolic coupling, nutrient competition, etc.) or from environmental filtration (such as responding similarly to environmental factors or due to physical separation) 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…A higher rate of horizontal gene transfer is also linked to the industrialization era, which might facilitate acquiring of new functions and adaptation to the change in the environment (Groussin et al, 2021;Lau et al, 2021). A pioneering study shows that the skin microbiome is altered in the urban population and this alteration changes the physiological response of the skin and is implicated in skinrelated diseases (Lau et al, 2021;Wang et al, 2021c).…”
Section: Urbanization and Microbiome Compositionmentioning
confidence: 99%